Minimally invasive resin infiltration of post orthodontic lesions: A Case Report. - ABDULLAH, ZOHA; ARUMUGAM, I. MEIGNANA; KUMAR.R, PRADEEP; SAKTHI, SRI (The journal of contemporary issues in business and government, 2020)
The earliest evidence of demineralization on the smooth enamel surface of a crown is a white spot lesion. It is one of the most commonly encountered esthetic problems post orthodontic treatment. The conventional treatment of these white spot lesions includes topical fluoride application, improving the oral hygiene, and use of remineralizing agents. This article uses a minimally invasive novel approach to treat white spot lesions based on infiltration of enamel caries with low-viscosity light curing resins called infiltrants. This technique is a promising treatment modality for the prevention of caries progression and improving esthetics, by diminishing the opacity.